Studi Fenomenologi Budaya Perencanaan Keuangan Keluarga Musllim di Sidoarjo dan Surabaya - Ika Yunia Fauzia (Jurusan Akuntansi Politeknik Negeri Ujung Pandang, 2020)
Abstrac:This paper is interested in exploring the phenomenon of planning and management of the Muslim family finances in Sidoarjo and Surabaya. The Muslim families that this paper focuses on are those with high religious commitment judged from their regular attendance to religious rituals and gatherings such as Majlis Taklim and the likes. The towns of Sidoarjo and Surabaya are being chosen to obtain specific findings on the one hand, and to have a better picture of the culture of wealth management among the urban Muslims on the other. The study is qualitative in its methods, and phenomenological in its analysis. Data were extracted from 20 informants, 7 of whom are categorised as lower income, 8 are middle income, and 5 are upper income laborers. One of the findings that this paper comes about is the fact that better understanding to the teachings of religion obtained from religious gatherings does not necessarily make a family better in its financial planning and management. On the other hand, with some exceptions, many informants among the lower classes are capable of managing their household and running their finances well making them better off to prepare their future needs. Keywords: Planning, management, Muslim household, family Abstrak:Fenomena perencanaan dan pengelolaan keuangan rumah tangga keluarga Muslim selalu menarik untuk dibahas, terlebih keluarga dengan intensitas yang tinggi untuk mempelajari agama Islam melalui Majlis Taklim dan kajian-kajian agama lainnya. Penelitian ini membatasi lokasi hanya di Surabaya dan Sidoarjo saja, untuk mendapatkan temuan yang spesifik. Penelitian dilakukan dengan metode kualitatatif, dengan alat analisis fenomenologi. Data digali dari 20 informan, dengan spesifikasi 7 informan dari kategori pendapatan kelas bawah, 8 informan dari kategori pendapatan kelas menengah dan 5 informan dari kategori pendapatan kelas atas. Dari beberapa informan tersebut dihasilkan satu temuan, bahwa semakin tinggi pemahaman keagamaan yang didapatkan dari kajian-kajian agama tidak serta merta menjadikan sebuah keluarga cerdas dalam merencanakan dan mengelola keuangan rumah tangga mereka. Walaupun ada beberapa pengecualian, yaitu terdapat informan di kalangan bawah yang mampu memanaj keuangan rumah tangga mereka dengan baik sehingga mereka bisa mempersiapkan kebutuhan masa depan dengan bijak.Kata Kunci: Perencanaan, pengelolaan, rumah tangga Muslim, keluarga